The Relationship Between the Growth of Leaves, Stems, and Roots of Elephant Foot Yam at Each Application of Bokashi and NPK Fertilizer - L. Limbongan, Yusuf (Journal of World Science, 2023)
Research on the relationship between the growth of leaves, stems, and roots of elephantiasis plants in each application of bokashi fertilizer and NPK fertilizer was carried out from July to October 2022 in Rante Dengen, Lembang Karre Limbong, Nanggala District, North Toraja Regency. This study aimed to determine the relationship between the growth of leaves, stems, and roots of elephantiasis after each application of bokashi from chicken waste and NPK fertilizer. The experiment used a randomized group design (RB) with two treatment factors: liquid organic fertilizer from chicken waste and NPK. The results showed that giving bokashi at a dose of 400 g/plant gave the best results, and NPK fertilizer at a dose of 20 g/plant was also the treatment that gave the best results. The relationship pattern between leaf, stem and root growth variables is linear. The variables that most contribute to the dry weight gain of plants are stem diameter and akare's volume. Our sincere gratitude goes to DRPM, Directorate General of Higher Education, Ministry of Education and Culture (Kemendikbud Ristek DIKTI), Indonesia, as well as the Indonesian Christian University of Toraja, for their financial support throughout this study.